Phylogenetic relationships among the Iranian Triticum diploid gene pool as inferred from the loci Acc1 and Pgk1 - Nasernakhaei, Fatemeh; Rahiminejad, Mohammad Reza; Saeidi, Hojjatollah; Tavassoli, Manoochehr (Phytotaxa, 2015)
In this study, 129 individuals belonging to the Iranian wild diploid Triticum gene pool were screened using PCR-SSCP based on Acc1 and Pgk1 loci. Sequencing of the representatives of different SSCP patterns allowed for detection of three haplotypes for each of the loci. The phylogenetic relationships among the Iranian wild diploid Triticum haplotypes and related genera were analyzed using DNA sequences from these two single copy loci. Despite previous reports that recommended the usefulness of nuclear single copy genes for phylogenetic inference, the Bayesian and parsimony analyses carried out in this study showed that these two loci were not applicable tools in the phylogeny reconstruction of diploid Triticum gene pool. Thus, our findings confirm that phylogenetic relationships among recently diverged species are often difficult to resolve due to insufficient phylogenetic signal in available markers and/or conflict among gene trees.